THE EFFECT OF HOME STUDY IMPLEMENTATION ON STUDENTS' LEARNING MOTIVATION IN CLASS IX SMPIT GITA WIRABANGSA (Jurnal Sosial Humaniora dan Pendidikan, 2022)
Purpose study this is for know influence implementation study at home to motivation study students at the Class IX SMPIT Gita Wirabangsa. This study uses a survey method with a quantitative approach. Data collection techniques using the questionnaire given to student force class IX with sample 20% of population, sample used researcher as many as 314 students. The results showed that the implementation of home learning activities had a positive effect on students' learning motivation, and the correlation value of home learning on students' learning motivation was in a weak position.